Management of temporomandibular joint Coccidioidomycosis. Issue 6 (1st November 2016) - Hammoudeh, Ziyad S.; Lettieri, Salvatore
Abstract : Purpose : The aim of this report was to present the first known case of coccidioidomycosis involving the temporomandibular joint, review the literature regarding dissemination to the mandible, and to provide treatment recommendations for this challenging condition. Methods: Coccidioidomycosis of the mandibular condyle was identified in a 30-year-old Somali male residing in Arizona. Due to the difficulty of surgical access and the anticipated temporomandibular joint morbidity of radical condylar debridement, primary medical management was performed. Results: Marked symptomatic improvement was observed after 10 days of IV antifungal therapy. Resolution of the abscess with residual bony destruction was observed on CT scan. Based on the results of this patient and review of the literature, an algorithm is presented to help guide management of coccidioidomycosis dissemination to the mandible. Conclusion: Prolonged antifungal therapy should be attempted for initial management of a Coccidioides abscess involving the condyle with early surgical intervention reserved for the more easily accessible and less functionally compromising portions of the mandible.